Overexpression of Bacterial mtlD Gene in Peanut Improves Drought Tolerance through Accumulation of Mannitol - Tengale Dipak Bhauso; Thankappan Radhakrishnan; Abhay Kumar; Gyan Prakash Mishra; Jentilal Ramjibhai Dobaria; Kirankumar Patel; Manchikatla Venkat Rajam (The Scientific World Journal)
In the changing global environmental scenarios, water scarcity and recurrent drought impose huge reductions to the peanut (Arachis hypogaea L.) crop yield. In plants, osmotic adjustments associated with efficient free radical scavenging ability during abiotic stress are important components of stress tolerance mechanisms. Mannitol, a compatible solute, is known to scavenge hydroxyl radicals generated during various abiotic stresses, thereby conferring tolerance to water-deficit stress in many plant species. However, peanut plant is not known to synthesize mannitol. Therefore, bacterial mtlD gene coding for mannitol 1-phosphate dehydrogenase under the control of constitutive promoter CaMV35S was introduced and overexpressed in the peanut cv. GG 20 using Agrobacterium tumefaciens-mediated transformation. A total of eight independent transgenic events were confirmed at molecular level by PCR, Southern blotting, and RT-PCR. Transgenic lines had increased amount of mannitol and exhibited enhanced tolerance in response to water-deficit stress. Improved performance of the mtlD transgenics was indicated by excised-leaf water loss assay and relative water content under water-deficit stress. Better performance of transgenics was due to the ability of the plants to synthesize mannitol. However, regulation of mtlD gene expression in transgenic plants remains to be elucidated.